Motivations of adherence to the practise of academy gymnastic - K.F. Rocha (Desafio Singular, 2008)
The purpose of this study was to analyse the main motivatians of adherence to Academy gymnastic and to verify the relationship between age, sex and adherence motivations. The Sample was compound by 250 individuals (181 feminine/69 masculine), practitioners of aerobic gymnastic or one of its variants, in a minimum of practise of three times per week, through the period of time of at least three non - stoppable months, in eight gyms situated in the city of Montes Claros-MG. The data was researched by the use of a questionary, created and validated for this study, aiming to receive information related to sex, age and interviewee's intention of practise. The statistic analysis was formed and based in a delineation and tracing of the sample, in other words, based in a descriptive analysis and comparative analysis between groups, using the x2 test. This statistical test demonstrated a non - significant statistic between Adherence motivations and sex or age of the study sample. The result's analysis lead to the conclusion that, independently of sex and age of the interviewees, the motive behind the practise of academy gymnastic is the image improvement followed by the necessity of having a life's quality.